A Partial Bison (Bison cf. B. latifrons) Skeleton from Chuchi Lake, and its Implications for the Middle Wisconsinan Environment of Central British Columbia - Harington, C.; Plouffe, Alain; Jetté, Hélène (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1996)
ABSTRACTFragmentary but massive left and right horncores, found with eight post-cranial bones, from a clay unit underlying a diamicton of the last (Fraser) glaciation at Chuchi Lake, British Columbia probably represents an individual giant bison (Bison cf. B. latifrons). A sample of bone from one of the horncores yielded an accelerator mass spectrometry (AMS) radiocarbon date of 30 740 ± 220 BP, whereas overlapping dates from two other laboratories on an associated humerus are 34 800 ± 420 BP and 35 480 ± 1080 BP. Despite the discrepancy between horncore and humerus dates, they are in accord with the suspected stratigraphie age of the clay unit whence they came. Analysis of pollen from that clay unit indicates that bison with massive horns once occupied an open forest in the vicinity. Probably giant bison and Columbian mammoths (incorporating paleoenvironmental evidence found with the nearby, penecontemporaneous Babine Lake mammoth) shared lake-dotted open forest to shrub tundra range in what is now central British Columbia toward the close of the Middle Wisconsinan (Olympia Nonglacial Interval). The Chuchi Lake specimen is important because it is the first indication of giant bison from British Columbia, and it appears to be one of the latest known survivors of this species.